A Sec-Dependent Effector from “Candidatus Phytoplasma ziziphi” Suppresses Plant Immunity and Contributes to Pathogenicity - Cui-Ping Wan; Fu-Xin He; Wei Zhang; Qian Xu; Qi-Liang Zhu; Chuan-Sheng Song (Biology)
Jujube witches’ broom (JWB) disease, caused by Candidatus Phytoplasma ziziphi (Ca. P. ziziphi), severely threatens the production of Chinese jujube (Ziziphus jujuba Mill.). Emerging evidence highlights the critical role of phytoplasma-secreted effectors in pathogenesis, though few have been functionally characterized. Here, we identified a Sec-dependent effector, JWB790, from Ca. P. ziziphi, which was shown to suppress plant immunity. Through transient expression assays in Nicotiana benthamiana, pathogen inoculation assays, the generation of transgenic Arabidopsis thaliana plants, and RNA-seq-based transcriptomic profiling, we systematically investigated the virulence function of JWB790. Our findings revealed that JWB790 is highly expressed in JWB-infected tissues. The transient expression of JWB790 in N. benthamiana suppressed BAX-induced cell death and H2O2 accumulation. Furthermore, the stable overexpression of JWB790 in A. thaliana compromised disease resistance, accompanied by reduced H2O2 accumulation and callose deposition triggered by flg22. Additionally, the RNA-seq analysis of JWB790 transgenic Arabidopsis plants indicated that the overexpression of JWB790 altered the expression of biotic stress-related genes. In summary, JWB790 is a virulence factor that suppresses plant immunity and promotes pathogen proliferation. These results advance our understanding of Ca. P. ziziphi pathogenesis.